2022
DOI: 10.3390/nu14030579
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylethanolamine Affects Lipid Accumulation and Metabolism in a Human Liver-Derived Cell Line

Abstract: The physiological functions of lysophosphatidylethanolamine (lysoPE) have not been fully elucidated. In this study, the effects of lysoPE on lipogenesis and lipolysis were investigated in a cultured human liver-derived cell line. The intracellular lipid profile was investigated in detail using liquid chromatography–tandem mass spectrometry (LC-MS/MS) to better understand the underlying mechanism. The expression of genes related to lipid metabolism and catabolism was analyzed using real-time PCR. LysoPE supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…A recent study reported that LPE supplementation induces enhanced cellular lipid droplet formation and increased lipid profiles, including TG-, CE-, PE-, LPE-, and PC-containing linoleic acyl triacylglycerol in human liver-derived cell line C3A. 46 The increased LPC and LPE contents observed in the present study could be potentially attributable to increased biosynthesis or increased PLA2 activity, which needs further studies.…”
Section: Discussionmentioning
confidence: 55%
“…A recent study reported that LPE supplementation induces enhanced cellular lipid droplet formation and increased lipid profiles, including TG-, CE-, PE-, LPE-, and PC-containing linoleic acyl triacylglycerol in human liver-derived cell line C3A. 46 The increased LPC and LPE contents observed in the present study could be potentially attributable to increased biosynthesis or increased PLA2 activity, which needs further studies.…”
Section: Discussionmentioning
confidence: 55%
“…As a family, lysophospholipids play a role as precursors for membrane biosynthesis and as signaling molecules, promoting plaque formation, which leads to atherosclerosis [ 89 , 90 , 91 , 92 , 93 ]. LysoPE (18:2) in particular, has been shown to induce lipid droplet formation and accumulation (within hepatocytes) and is reported in cases of non-ST-elevation myocardial infarction (NSTEMI) [ 94 , 95 ]. Thus, the suppression of this metabolite by probiotic supplementation may result in a reduction of the precursors to cardiovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, through an in-depth analysis of the basal, higher-fat, and higher-fat+probiotic cohorts, we discovered that with probiotic supplementation, some potentially aberrant metabolites identified in the higher-fat cohort tissues (notably, S-adenosylhomocysteine and glutathione in the brain cortex, indoxyl sulfate in the kidney, and LysoPE (18:2) in the heart) revert to levels associated with those found in pigs fed a healthy, nutritionally balanced diet. While it remains unknown as to why these higher-fat altered metabolites are particularly sensitive to probiotic supplementation, we can speculate that their reversion to a healthy-associated metabotype may promote healthy neurocognitive function, clear toxic by-products of protein putrefaction, and reduce hallmarks of atherosclerosis [ 28 , 29 , 30 , 31 , 36 , 37 , 52 , 53 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Coupled together, the reversion of the intracellular concentration of these metabolites to a level akin to a healthy diet depicts the beneficial nature of probiotic supplementation and may show its usefulness as a prophylactic approach to address obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, LPC 16:0 and LPC 18:0 promote lipid accumulation and apoptosis [ 62 , 63 ]. LPE 18:2 activates G-protein-coupled receptor signaling and increases lipid accumulation [ 65 , 66 ], while serum LPE 16:0 associates with diabetes mellitus [ 67 ]. LPG is the agonist of G-protein-coupled receptor 55 and induces inflammation in macrophages [ 68 ].…”
Section: Discussionmentioning
confidence: 99%